Development of a reliable analytical method for the precise extractive spectrophotometric determination of cadmium(II) by using of chromogenic reagent: analysis of real samples. Issue 16 (16th December 2022) - Nalawade, Avinash M.; Nalawade, Rekha A.; Shejwal, Rajendra V.; Kamble, Ganesh S.; Ling, Yong-Chein; Anuse, Mansing A.
ABSTRACT: A new analytical reagent N'', N'''-bis[(E)-(4-fluorophenyl)methylidene] thiocarbonohydrazide: bis-(4-fluoroPM)TCH was used for simple, fast and synergistic extractive spectrophotometric determination of cadmium(II). Cadmium(II) forms stable faint yellow coloured ternary complex at room temperature with reagent and pyridine as synergent having composition 1:2:2 (M:L:Py) at pH 4.0. The absorbance of coloured organic layer in iso amyl acetate is measured spectrophotometrically at 390 nm against reagent blank. In the extraction of cadmium(II), various affecting factors including the solution pH, reagent concentration, synergent concentration, equilibrium time, colour stability and effect of foreign ions are optimised. Beer's law is obeyed in the concentration range 10–40 μg mL −1 of cadmium(II) and optimum range of 15–35 μg mL −1 of the metal as evaluated from Ringbom's plot. Molar absorptivity and Sandell's sensitivity value of complex in amyl acetate were 18, 660 lit/mol cm and 6.0 × 10 −3  μg/cm 2, respectively. The composition of cadmium(II)–bis-(4-fluoroPM)TCH–pyridine adduct was established by slope ratio, mole ratio and Job's method. Effects of foreign ions were also studied and use of suitable masking agent enhances the selectivity of method. Method has been successfully applied for determination of cadmium(II) in binary and synthetic mixtures, thin films, pharmaceuticals, coatings of ships, alloys, weeds in water and spiked water samples. The results obtained of proposed method were judged by using AAS for testing the validity of method. All the obtained results indicate a reliable, precise and fast analytical method for the extraction and quantification of trace levels of cadmium(II) from various synthetic and real samples without the use of sophisticated instrumentation and procedure.